2017
DOI: 10.5380/cep.v34i2.53138
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Starch From Avocado Seed (Persea Americana Mill)

Abstract: The extraction and characterization of avocado starch isolated from seeds (Persea americana Mill) were studied. The starch was extracted by steeping, wet grinding and sedimentation process and calculated its yield. Isolated starch was then characterized for chemical composition, morphology and granules size distribution, X-ray diff raction an mid-infrared spectra, swelling powder and solubility, pasting and thermal properties and clarity and syneresis behavior. The starch yield was 42.2%. The results showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
7
9
1
1
Order By: Relevance
“…These characteristics were also observed in tamarind starch by Kaur and Singh (2016) and Lychee kernel starch by Thory and Sandhu (2017). They are also consistent with the results obtained by Builders et al (2010), Santos et al (2016) and Silva et al (2017) on ASS.…”
Section: Morphological Characteristics Of Avocado Seed Starch Granulessupporting
confidence: 91%
See 2 more Smart Citations
“…These characteristics were also observed in tamarind starch by Kaur and Singh (2016) and Lychee kernel starch by Thory and Sandhu (2017). They are also consistent with the results obtained by Builders et al (2010), Santos et al (2016) and Silva et al (2017) on ASS.…”
Section: Morphological Characteristics Of Avocado Seed Starch Granulessupporting
confidence: 91%
“…ASS obtained a syneresis of 42.5% after 7 cycles. Builders et al (2010) in their studies found, after 4 cycles, a value of approximately 73% in ASS and Santos et al (2016) obtained 29.1% syneresis after 4 refrigeration cycles. This information indicates that avocado starch would not be suitable for using in chilled foods.…”
Section: Paste Clarity and Syneresismentioning
confidence: 88%
See 1 more Smart Citation
“…The CONV starch shows a normal behavior with temperature increases (60-90 • C) showing an increase of solubility of 12.8 to 24.3%, WAC of 6.7 to 13.2 g/g and SP of 7.7 to 17.4 g/g. Similar results were presented by dos Santos et al [12], Chel-Guerreo [15] and Silva et al [26] with avocado seed starch obtained by conventional methods. Contrary to the MAE starches have completely different behavior when compared with CONV starch and other authors.…”
Section: Solubility Swelling Power (Sp) and Water Absorption Capacity (Wac) Of Starchsupporting
confidence: 89%
“…Starch is a renewable biopolymer material that is entirely biodegradable, easy to handle, and widely available in nature, such as in the avocado [124,125]. Seeds have shown to contain a large amount of starch that can reach over 90%.…”
Section: Starch Applicabilitymentioning
confidence: 99%